A STUDY OF MICROSTRUCTURAL CHANGES OF MEAT PRODUCTS FROM REINDEER MEAT WITH THE ADDITION OF JERUSALEM ARTICHOKE POWDER - Inessa Aleksandrovna Zachesova; Stanislav Viktorovich Kolobov; Victoria Alexandrovna Pchelkina (Современная наука и инновации)
The article presents the results of histological study of samples of semi-finished products of reindeer meat with the introduction of Jerusalem artichoke powder in different quantities. The influence of the amount of Jerusalem artichoke powder and heat treatment on the microstructure of semi-finished products is considered.